Genetic variants affecting equivalent protein family positions reflect human diversity - Raimondi, Francesco; Betts, Matthew J.; Lu, Qianhao; Russell, Robert B. (Scientific reports, 2017)
Members of diverse protein families often perform overlapping or redundant functions meaning that different variations within them could reflect differences between individual organisms. We investigated likely functional positions within aligned protein families that contained a significant enrichment of nonsynonymous variants in genomes of healthy individuals. We identified more than a thousand enriched positions across hundreds of family alignments with roles indicative of mammalian individuality, including sensory perception and the immune system. The most significant position is the Arginine from the Olfactory receptor “DRY” motif, which has more variants in healthy individuals than all other positions in the proteome. Odorant binding data suggests that these variants lead to receptor inactivity, and they are mostly mutually exclusive with other loss-of-function (stop/frameshift) variants. Some DRY Arginine variants correlate with smell preferences in sub-populations and all 2,504 humans studied contain a unique spectrum of active and inactive receptors. The many other variant enriched positions, across hundreds of other families might also provide insights into individual differences.